THE IMPACT OF GENERAL HEALTH ON COGNITIVE FUNCTION (Experimental biology, 2026)
The study examined the effect of cognitive load on the bioelectric activity of the brain and the functional connections between cortical regions in healthy students and students with iron deficiency anemia using electroencephalography (EEG).The study involved healthy students and students with iron deficiency anemia, who were divided into two groups. The EEG was recorded in a standardized functional mode before and after completing the cognitive task, spectral analysis of alpha (8-13 Hz) and theta (4-7 Hz) rhythms was performed, as well as cross-correlation analysis, which is a type of correlation analysis. The participants completed a five-minute oral score task to assess their cognitive load.The results showed that spectral parameters were maintained in both groups until the cognitive task was completed, and during sensory stimulation, a decrease in the total power of the alpha rhythm and theta index was detected in the group with iron deficiency anemia. After completing the cognitive task, the healthy group demonstrated effective recovery of the alpha rhythm, restriction of the theta rhythm, and preservation of harmonious functional connections between areas of the cerebral cortex. In the group with iron deficiency anemia, insufficient recovery of alpha synchronization and an excessive increase in theta rhythm were detected. Correlation analysis revealed that the frontal regions have a weaker connection with the central and temporal regions. This describes a disruption in the integration of neural networks responsible for cognitive and executive functions, and suggests that it is associated with hypoxic and neurometabolic limitations.Spectral and cross-correlation indicators of alpha and theta rhythms are recommended for use as neurophysiological markers in assessing the functional state of the brain for cognitive load.
Keywords: electroencephalography, cognitive load, alpha rhythm, theta rhythm, iron deficiency anemia, spectral analysis, cross-correlation analysis.